2015
DOI: 10.1007/s11837-015-1350-7
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Peptides as Implant Functionalization Agents for Titanium Alloy Implants with Antimicrobial Properties

Abstract: Implant-associated infections can have severe effects on the longevity of implant devices and they also represent a major cause of implant failures. Treating these infections associated with implants by antibiotics is not always an effective strategy due to poor penetration rates of antibiotics into biofilms. Additionally, emerging antibiotic resistance poses serious concerns. There is an urge to develop effective antibacterial surfaces that prevent bacterial adhesion and proliferation. A novel class of bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 63 publications
0
74
0
1
Order By: Relevance
“…Furthermore, AMP surfaces displayed antimicrobial activity under dynamic growth conditions against S. gordonii 156) and under static growth conditions against Streptococcus mutans, Staphylococcus epidermidis and Escherichia coli 159) . This passive antimicrobial coating resisted hydrolytic and mechanical challenges and exhibited no significant release of peptides from the modified titanium surface.…”
Section: Antimicrobial Peptide Surfacesmentioning
confidence: 99%
“…Furthermore, AMP surfaces displayed antimicrobial activity under dynamic growth conditions against S. gordonii 156) and under static growth conditions against Streptococcus mutans, Staphylococcus epidermidis and Escherichia coli 159) . This passive antimicrobial coating resisted hydrolytic and mechanical challenges and exhibited no significant release of peptides from the modified titanium surface.…”
Section: Antimicrobial Peptide Surfacesmentioning
confidence: 99%
“…In our previous studies, we demonstrated that AMPs can be immobilized on titanium implant surfaces through the engineering of chimeric peptides that use molecular recognition to attach and self-assemble on the implant surface as a novel biomolecular-coating. 2426 A chimeric peptide is a bifunctional single-chain relatively short peptide when compared to biological proteins, and it joins two functional domains through an engineered spacer. The functional domain joined to the AMP for immobilization on implant surface is a peptide that is identified using combinatorial biology based molecular libraries, i.e., phage and cell surface display libraries.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Previous work has identified several titanium binding peptides (TiBP) that assemble onto the titanium surface with high affinity appropriate for the surface of titanium and titanium alloy-based implants. 24,25 Peptide-based self-immobilization strategies therefore offer an opportunity to overcome the limitations and challenges associated with covalent immobilization of antibacterial agents on implant surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid or reduce such undesirable consequences, some antibacterial agents (e.g., antimicrobial peptides, antibacterial ions, Ag nanoparticles etc.) were used for the fabrication of clinical antibacterial implants [6][7][8][9][10]. Although the sustained release of these substances could inhibit bacteria adhesion while ensuring the biosafety of implants against surrounding cells/tissues, the early stage (4-6 h) bacteria inhibition is not in well control to some extent.…”
Section: Introductionmentioning
confidence: 99%